Synthetic nanoprobes for biological hydrogen sulfide detection and imaging. Issue 4 (18th February 2022) - Zhou, Yingzhu; Mazur, Federico; Fan, Qingqing; Chandrawati, Rona
Abstract: Hydrogen sulfide (H2 S) is a gaseous molecule involved in multiple biological and physiological processes, including various diseases such as cancer and neurodegenerative disorders. This has led to the development of various analytical methods to monitor H2 S in biological settings. Among these, fluorescence‐based assays, specifically organic small‐molecule probes, have been thoroughly utilized. They offer good sensitivity and specificity as sensors, and noninvasive detection with high spatiotemporal resolution in in vitro and in vivo imaging. Despite attempts to decrease the rate of photobleaching and enhance the photostability of these dyes, they are still limited by low survival time and complex reagent pretreatment. Fortunately, nanotechnology has been applied to develop effective, highly sensitive, and specific fluorescent nanoprobes. Specifically, nanomaterial‐based H2 S probes have emerged as promising candidates for real‐time detection and imaging. In contrast to their organic molecule‐based counterparts, they offer higher versatility in imaging modes due to their unique optical properties, improved photostability and solubility within physiological fluids, as well as easily modifiable surfaces and tuneable structures for improved specificity. Recently, many nanomaterial‐based probes, ranging from inorganic nanoparticles to self‐assembled nanocomposites, have been developed. These have, for the most part, achieved sensitive and specific endogenous H2 S detection and in vivo imaging. In this review, we evaluate five different nanomaterials currently being researched to detect and image endogenous H2 S within the last 5 years. Furthermore, analytical methods associated with the various signal outputs, current challenges in H2 S nanoprobe design, and possible future research interests are outlined and discussed. Abstract : Current advances of nanomaterial‐based probes for in vitro and in vivo H2 S sensing and imaging. The existing challenges in developing H2 S nanoprobes and aspects that affect probe's performance are also discussed.